Preserving a Legacy: Ensuring the Access and Conservation of the Harold (Harry) G. Fowler (1950–2018) Ant Collection and Data - Wazema, Claudia Tiemi; Silva, Otávio Guilherme Morais Da; Magalhães, Fabrício Severo; Prado, Lívia Pires Do; Nagatani, Victor Hideki; Silva, Nathalia Sampaio Da; Vaz, Juliana Aparecida Calisto; Silva, Paulo Henrique Alves Da; Ulysséa, Mônica Antunes; Camacho, Gabriela Procópio; Freitas, Gisely Da Silva; Brandão, Carlos Roberto Ferreira; et al. (Zootaxa, 2024)
Biological collections are important repositories of biodiversity, as they include various types of data potentially useful to different areas of science and can contribute to the establishment of biodiversity conservation policies. For a long time, scientific collections were considered only as physical databases; in this context Harold G. Fowler (1950–2018) built an ant collection at the Universidade Estadual Paulista, campus Rio Claro (São Paulo state, Brazil), over the course of a 34-year career, comprising around 20,000 ant specimens. Most specimens came from the Brazilian Atlantic Forest, but many others came from distinct locations in Brazil and abroad. After his death, the collection was left without the necessary curatorial care for a period of time, which required a project to be conceived for its recovery and conservation, with the goal of incorporating it to the Zoology Museum of the University of São Paulo (MZSP). In addition to applying modern technical curation protocols, other activities such as checking, material identification and digitization of the information contained on the sample labels were carried out, forming an accurate database. This process enabled the identification of new distribution records and the discovery of possible undescribed species and unpublished natural history data. After validating this information, we counted 524 valid species and 201 morphospecies belonging to 105 genera and 10 subfamilies. In addition, we integrated technical curation activities with scientific outreach to draw the general public’s attention to the importance of biological collections, thus fostering interest in science, biodiversity and nature conservation. Our work highlights the importance of preserving the areas sampled by Fowler’s research group. The preservation of vouchers using curatorial practices reinforces the role of scientific collections as important tools for the study, understanding and preservation of biodiversity.